2021
DOI: 10.3390/biomedicines9060687
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in NAFLD–NASH–HCC Transition—Focus on NADPH Oxidases

Abstract: A peculiar role for oxidative stress in non-alcoholic fatty liver disease (NAFLD) and its transition to the inflammatory complication non-alcoholic steatohepatitis (NASH), as well as in its threatening evolution to hepatocellular carcinoma (HCC), is supported by numerous experimental and clinical studies. NADPH oxidases (NOXs) are enzymes producing reactive oxygen species (ROS), whose abundance in liver cells is closely related to inflammation and immune responses. Here, we reviewed recent findings regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 85 publications
0
48
0
Order By: Relevance
“…ROS can induce the proliferation and migration of HSCs, collagen accumulation, and the formation of liver fibrosis [67,68]. NADPH oxidase 4 (NOX4)-derived ROS are the main source of oxidative stress in NAFLD, and they contribute to hepatic injury [69]. In the present study, a high-fat diet upregulated the protein expression of NOX4, with high levels of superoxide anion production and MDA observed in the zebrafish liver.…”
Section: Discussionmentioning
confidence: 50%
“…ROS can induce the proliferation and migration of HSCs, collagen accumulation, and the formation of liver fibrosis [67,68]. NADPH oxidase 4 (NOX4)-derived ROS are the main source of oxidative stress in NAFLD, and they contribute to hepatic injury [69]. In the present study, a high-fat diet upregulated the protein expression of NOX4, with high levels of superoxide anion production and MDA observed in the zebrafish liver.…”
Section: Discussionmentioning
confidence: 50%
“…Since oxidative stress plays a pivotal role in fibrogenesis and it has been demonstrated that OC displays antioxidant effect on various cell lines ( 5 ), we investigated its effect on oxidative stress-related pathways. Investigating oxidative stress is of particular relevance in fibrosis, since it well known that the pro-oxidative activity of the NOXs is increasing upon the activation of the receptor for advanced glycation endproducts (RAGE), caused by its interaction with ligands induced during inflammation ( 11 ). Beside NOXs, RAGE can in turn activate the inflammatory nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway, leading to a vicious cycle in which oxidative stress and inflammation generate a sustained pro-fibrotic response by reciprocal synergic actions ( 11 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Investigating oxidative stress is of particular relevance in fibrosis, since it well known that the pro-oxidative activity of the NOXs is increasing upon the activation of the receptor for advanced glycation endproducts (RAGE), caused by its interaction with ligands induced during inflammation ( 11 ). Beside NOXs, RAGE can in turn activate the inflammatory nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway, leading to a vicious cycle in which oxidative stress and inflammation generate a sustained pro-fibrotic response by reciprocal synergic actions ( 11 , 43 ). In this context, we first observed that OC treatment downregulated the mRNA expression of two isoforms of NOXs i.e., NOX1 and NOX4, peculiar enzymes involved in hepatic ROS production, in TGF-β1-activated LX2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noticed that the lack of HNF4α in the liver seems to be associated with impaired lipid, glucose, cholesterol, and BA homeostasis and is considered as a pivotal regulator of hepatic transcriptome. Some of the genes downregulated in HNF4α-liver knockout mice in a male-specific manner are Cyp7b1, involved in the synthesis of BAs, Hsd3b4 (hydroxysteroid dehydrogenase 4), and Nox4 (NADPH oxidase 4), involved in oxidative stress [ 110 , 111 ].…”
Section: Pxr-related Gender Differences In Chronic Liver Diseasementioning
confidence: 99%